Odpowiedzi

Najlepsza Odpowiedź!
2010-03-23T17:28:03+01:00
3(x+2)-5 ≥ 4x-2(1-x)
3x+6-5≥4x-2+x
3x-4x-x≥-2-6+5
-2x≥-3
x≤1,5



2x-(1-x) < 2(x+3)+x-1
2x-1+x<2x+6+x-1
2x+x-2x-x<6-1+1
0≠6



2- (x+4/5) ≤ 4- (2x+3/5)
2-x-⅘≤4-2x-⅗
-x+2x≤4-⅗-2+⅘
x≤2,2
2010-03-23T17:32:12+01:00
3(x+2)-5 ≥ 4x-2(1-x)
3x+6-5 ≥ 4x-2+2x
3x+1≥6x-2
3x-6x≥-2-1
-3x≥-3 /-3
x≤1

2x-(1-x) < 2(x+3)+x-1
2x-1+x<2x+6+x-1
3x-1< 3x+5
3x-3x<6
0<6

2- (x+4/5) ≤ 4- (2x+3/5)
2-x-4/5≤4-2x-3/5
-x+ 1i1/5≤3i2/5-2x
-x+2x≤3 i 2/5 -1i 1/5
x≤2 i 1/5
2010-03-23T17:39:14+01:00
3(x+2)-5 ≥ 4x-2(1-x)
3x+6-5 ≥ 4x-2+2x
3x-4x-2x ≥ -2+5-6
-3x ≥ -3 /: -3
x ≤ 1

2x-(1-x) < 2(x+3) +x-1
2x-1+x < 2x+6+x-1
3x-2x-x < 1+6-1
x < 6

2-(x+4/5) ≤ 4-(2x+3/5)
2-x-0,8 ≤ 4-2x-0,6
-x+2x ≤-0,6+4+0,8-2
x ≤ 2,2